The Relationship Between Culture and Language: An Anthropological Linguistics Study - Susianti, Hartanti Woro; Moon, Yuliana Jetia; Budi, Imanuel Setyo (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2024)
The interplay between culture and language is a central theme in anthropological linguistics. Culture encompasses values, beliefs, norms, and traditions passed down through generations, and language plays a fundamental role in expressing and preserving these cultural elements. This paper explores the reciprocal relationship between language and culture, illustrating how language not only reflects but also shapes the social and cultural realities of a community. By examining various examples, such as the use of honorifics in Japanese culture and the transmission of oral traditions in indigenous communities, the study highlights the role of language as a medium for cultural continuity. Additionally, it delves into how cultural changes, such as technological advancements, lead to the evolution of language, especially in the development of new vocabulary. Through this analysis, the paper aims to provide a comprehensive understanding of how language and culture mutually influence each other, facilitating the ongoing process of cultural preservation and transformation.